Aplicabilidade de uma máquina teste eletrodinâmica a molas não lineares - Bastos, Leopoldo Eurico Gonçalves (1969)
An eletrodynamic system for testing fatigue in springs is represented by a model which has two degrees of freedom. The simulation of the tester by a two degrees af freedom system with restoring force F =(α+βx²)x is made on an analog computer EAI – TR48 DES – 30. The favorable values of the spring deflection ratio y1 /(y2 - y1) the frequency of the exciting force, and y2 the amplitude of motion of the mass m2, as function of the mass ratio m2/m1, are determined to the execution of the test. The results are compared with those of the analytic solution for the case of linear springs (β = O). The favorable values of the spring deflection ratio y1 /(y2 - y1), the frequency of the exciting force, and y2 the amplitude ofmotion of the mass m2, as function of the mass ratio m2 /m1, are determined to the execution of the test. The results are compared with those of the analytic solution for the case of linear springs (β = 0).